The legal reasoning skills. Theoretical considerations - Lisett D. Páez Cuba (Revista MENDIVE, 2014)
This research analyzes the legal reasoning as essential skills to the teaching - learning process of law. This approach is based on a theoretical systematization of the Theory of Legal Argumentation (TLA) that allows the conception of law as an argumentative act itself. It also determines, as a new element, the inclusion of legal argumentation as the final phase of the law cycle, which has particular impact on the teaching of this science. In this regard, the proposal of three skills of legal reasoning is made: interpreting the law, enforce the rule of law and legally argue the legal decision.